Four Middle English Charlemagne romances: a revaluation of the non-cyclic verse texts and the holograph Sir Ferumbras - Shepherd, S (1988)
Four Middle English Charlemagne Romances are examined with the intention of disproving conventional claims that English romances of the 'Matter of France' are typically undistinguished. The manuscript of the Ashmole Sir Ferumbras is a holograph; preserved with it, on sheets which originally formed the binding, is a portion of the poem's rough draft. Comparison of the draft with the fair copy reveals something of the romancer's translational and compositional method, and illustrates well his enthusiasm for, and ability occasionally to improve upon, his French source. The fragment of The Song of Roland displays some sensitivity to the heroic essence of its famous French model. The poem also displays, however, a free, sensitive, sometimes eloquent and technically complex, adaptation of notable features of that model. The Sege of Melayne has been recognized for its energy; but extensive studies of the poem appear to have been prevented by an inability to account for the poem's lack of known sources and its use of extraordinary episodes and unusual narrative techniques. Analogues and possible influences do, however, exist; and most reveal the poem's remarkable affinity with propagandistic crusading literature. This affinity goes some way toward explaining, and allowing us to appreciate, the poem's unusual features. Rauf Coilyear is unusually described as a competent and straightforwardly humorous tale similar in spirit to its analogues. A closer look, however, shows the humour to be complicated by the seriousness of a social critique; at times the hero's experiences is far from laughable. There is, in fact, some similarity, both of incident and theme, with the best poems of the 'Gawain-group'. That a comparison with such poems (and, indeed, with 'serious' elements in the other Charlemagne romances) can convincingly be made suggests that our expectations of the poem's literary significance should be revised accordingly.